Competencies, Self‐awareness, and Practice: Notes on My Reading of Chapters 5–7. Issue 168 (25th January 2021) - Hall, Melvin E.
Abstract: As part of this NDE issue with its focus on the 2018 American Evaluation Association (AEA) Evaluator Competencies, this chapter discusses the content and delivery of material in Chapters 5 through 7. The reviewed chapters, and therefore this article, address potential uses of the 2018 AEA Evaluator Competencies to promote professional self‐knowledge, enhance education and training programs for new and in‐service professionals, and facilitate evaluator and evaluation pursuit of social justice. This chapter will assist readers of these chapters by providing a review from the perspective of an experienced evaluation professional. Its critiques and related admonitions to the profession are the sole and independent opinions of the author.